Searching For Signs of Life in Ontario Universities: An Innovative Method for Evaluating Biodiversity Integration within University Curricula - McCallum, Jenn; Elliott, Paul; McIntosh, Terese (Canadian Journal of Higher Education, 2017)
This study investigates the degree to which biodiversity concepts are included within university curricula in Ontario and provides a baseline for tracking this. A keyword search of undergraduate and graduate academic calendars from six Ontario universities was conducted. A list of 28 relevant keywords was developed, and university program descriptors were searched for these keywords, while considering core and elective courses within each program. Almost half (49.5%) of the 386 undergraduate programs, and 29.4% of the 327 graduate programs featured biodiversity keywords. Science programs showed the highest degree of integration (74.5% for undergraduate and 37.4% for graduate programs), followed by business programs (57.6% and 38.4%, respectively). The arts and social sciences showed the least biodiversity integration (25.8% of undergraduate and 21.0% of graduate programs). This research method provides a depth of understanding of biodiversity integration within university curricula, although the analysis is limited to the content provided in academic calendars.